2017
DOI: 10.1186/s12885-017-3310-9
|View full text |Cite|
|
Sign up to set email alerts
|

Circulating blood levels of IL-6, IFN-γ, and IL-10 as potential diagnostic biomarkers in gastric cancer: a controlled study

Abstract: BackgroundGastric adenocarcinoma is the third most common cause of cancer-associated death worldwide. Helicobacter pylori infection activates a signaling cascade that induces production of cytokines and chemokines involved in the chronic inflammatory response that drives carcinogenesis. We evaluated circulating cytokines and chemokines as potential diagnostic biomarkers for gastric cancer.MethodsWe included 201 healthy controls and 162 patients with distal gastric cancer who underwent primary surgical resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
1
13

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 37 publications
4
58
1
13
Order By: Relevance
“…This assumption is supported by a study in which increased systemic levels of IL-10 and decreased levels of IL-4 have been found investigating EAC and ESCC together [21]. Conversely, in gastric cancers increased levels of both serum IL-10 and IL-4 have been reported [22][23][24][25][26]. These findings emphasize the use of both systemic IL-10 and IL-4 as potential biomarkers in EACs.…”
Section: Plos Onementioning
confidence: 64%
See 1 more Smart Citation
“…This assumption is supported by a study in which increased systemic levels of IL-10 and decreased levels of IL-4 have been found investigating EAC and ESCC together [21]. Conversely, in gastric cancers increased levels of both serum IL-10 and IL-4 have been reported [22][23][24][25][26]. These findings emphasize the use of both systemic IL-10 and IL-4 as potential biomarkers in EACs.…”
Section: Plos Onementioning
confidence: 64%
“…On the other hand, anti-inflammatory cytokines like IL-4 and IL-10 have a predominantly regulatory function in the immune system [19,20]. Increased as well as decreased levels of IL-4 and IL-10 have been reported in esophageal and gastric cancers and their prognostic value remains uncertain [21][22][23][24][25][26]. However, one meta-analysis identified serum IL-10 as a negative prognostic marker in several gastrointestinal malignancies including colon and gastric cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of cytokines was calculated based on standard curves provided with the kits, and results were expressed in ng/ml. For ELISA all samples were tested in duplicate and the average values were used in the analysis (4) .…”
Section: Cytokine Assaysmentioning
confidence: 99%
“…Mortality rates are higher in Asian and Latin American countries, where cases are usually diagnosed at later stages, leading to very low survival rates. It arises more in men, than women (2:1), 95% of cases are adenocarcinomas which is the most common malignant tumor regardless of age, race or inclining factors presented by a patient (3,4) .…”
Section: Introductionmentioning
confidence: 99%
“…After publication of the original article [ 1 ] the authors found the following author names were incorrect and needed to be amended: In the original article, author Javier Torres’ name was presented as J. Torres. In the original article author Roberto Herrera-Goepfert’s first name was incorrectly presented as Ramón.…”
Section: Correctionmentioning
confidence: 99%